Aggregation behaviour of chiral ionic liquids - Schulz, Peter; Schneiders, Karola; Wasserscheid, Peter (Tetrahedron-Asymmetry, 2009)
The diastereomeric ionic liquid (IL) (1R,2S)-ephedrinium (RS)-methoxytrifluorophenylacetate 1 was synthesized and its aggregation behavior and diastereomeric interaction were investigated using two independent methods. The aggregation number of the IL in methylene chloride was determined by diffusion ordered NMR spectroscopy. Furthermore the concentration dependence of the signal split of the two diastereomeric ILs (1R,2S)-ephedrinium (R)-methoxytrifluorophenylacetate and (1R,2S)-ephedrinium (S)-methoxytrifluorophenylacetate was measured and could be linked to the aggregation number. © 2009 Elsevier Ltd. All rights reserved.